Probiótico (Bacillus amyloliquefaciens) e antimicrobiano melhorador de desempenho em dietas de leitões na fase de creche - Berteli, Carolina Ribeiro (2019)
Changes related to weaning are stressful factors and may cause reduced piglet growth, mainly due to the incidence of diarrhea. Considering the limitations to the use of antimicrobial performance enhancers, different strategies were proposed to maintain animal growth and performance. The objective of this study was to evaluate the effects of the use of probiotic (Bacillus amyloliquefaciens) on weaned piglets diet, associated or not with the use of antimicrobial performance enhancer (tiamulin). A total of 84 piglets with a mean age of 28 days were randomized in blocks and a factorial scheme 2 x 2, with four treatments, corresponding to the inclusion or not of performance improvement antibiotic (tiamulin 80% 150ppm) and probiotic (Bacillus amyloliquefaciens – 1x10 10 UFC/g). The treatments adopted were: T1 - basal diet (DB, control); T2 - DB + antimicrobial; T3 - DB + probiotic; T4 - DB + antimicrobial + probiotic. Avarage daily gain, feed intake and feed efficiency were calculated. The fecal score was monitored according to the method proposed by Guedes et al. Feces samples were collected for presence and counting analysis of Escherichia coli (Quinn et al.). Statistical analyzes were performed using software R and differences considered significant for P <0.05. For non-parametric data it was used the Friedman test and the Tukey test were used for the others. The absolute data of microbiological counting were logarithmized and analyzed in a descriptive way. The average daily feed intake was affected by the use of antimicrobial, while the use of probiotic did not result in significant effect. Weight gain and feed conversion were not affected by the use of antimicrobial or probiotic. The diarrhea score was significantly affected in the final phase, with lower scores for animals fed with antimicrobial and probiotic. In the descriptive evaluation of the E. coli count, there was a trend of higher fecal bacterial count over the experimental period in all treatments, more prominently in the samples from the animals that did not take probiotic. The use of probiotics (B. amyloliquefaciens) is a valid strategy to replace the use of antimicrobials for weaned pigs. The addition of probiotic keeped piglet consumption and performance in the early stages of life.